2015
DOI: 10.5588/ijtld.15.0102
|View full text |Cite
|
Sign up to set email alerts
|

Factors associated with diabetes mellitus among adults with tuberculosis in a large European city, 2000–2013

Abstract: DM prevalence among adults with TB in Barcelona is low and remained stable over the 14-year study period. However, TB patients with DM were potentially more infectious and their clinical management was more complicated.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

4
32
3
5

Year Published

2017
2017
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 23 publications
(44 citation statements)
references
References 0 publications
4
32
3
5
Order By: Relevance
“…Our finding was also comparable with the results of studies carried-out in Ethiopia (8.3%), Uganda (8.5%) and USA (11.4%)111220. However, DM prevalence among TB patients reported in this study was higher than the rates reported from China (6.3%), Spain (5.9%), Guinea-Bissau (2.8%) and Benin (1.9%); but lower than the rates reported from Taiwan (29.5%), Southern-Mexico (29.3%) and India (25.3%)13141516212223. Reason/s for the differences in prevalence might be due to disparities in patient background and disease burden.…”
Section: Discussioncontrasting
confidence: 68%
See 3 more Smart Citations
“…Our finding was also comparable with the results of studies carried-out in Ethiopia (8.3%), Uganda (8.5%) and USA (11.4%)111220. However, DM prevalence among TB patients reported in this study was higher than the rates reported from China (6.3%), Spain (5.9%), Guinea-Bissau (2.8%) and Benin (1.9%); but lower than the rates reported from Taiwan (29.5%), Southern-Mexico (29.3%) and India (25.3%)13141516212223. Reason/s for the differences in prevalence might be due to disparities in patient background and disease burden.…”
Section: Discussioncontrasting
confidence: 68%
“…In addition, the low DM prevalence observed in these settings may also be explained by the high burden of TB among younger persons, who in general have a lower incidence of DM than those aged (40 years or over)24. Furthermore, differences in dietary habits and the screening methods used for DM diagnosis might contribute to the variation in prevalence of DM among TB patients in various regions13141516212223.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…HIV coinfection and malnutrition were also reported as low risk factor for TBDM comorbidity [72, 95]. HIV coinfection with injection drug use (IDU) or without IDU was reported as low risk factor for TBDM coexistence [88]. TBDM comorbid patients were more likely to be PTB case, smear- positive, to have anti-TB drug resistance, to have cavitary lesions on chest x-ray, and to have high alanine transaminase (ALT) level [10, 25, 28, 30, 48, 54, 56, 88–89, 72, 76, 84, 88, 95, 100].…”
Section: Resultsmentioning
confidence: 99%